2020
DOI: 10.1051/e3sconf/202017801015
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of asynchronous motor operation modes for the correct selection of voltage regulation devices

Abstract: Many electrical appliances are used in production and in everyday life, which include elements that are extremely sensitive to voltage deviations from acceptable values. Failure in their work can cause equipment failure or a breakdown in technological processes. There are a number of technical solutions to solve this problem, one of which is the using of voltage control devices such as boost transformers. The principle of operation of booster transformers is the introduction of a longitudinal EMF into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…One of the main reasons for failure of electric motors is moisturization of winding insulation. For this reason, up to 20-30% of electric motors fail annually [1][2][3][4][5][6][7]. Our studies show that for air humidity of 100% and temperature of 35 °C, the insulation resistance R drops to a critical value of 0.5 MΩ within 9-10 days.…”
Section: Introductionmentioning
confidence: 94%
“…One of the main reasons for failure of electric motors is moisturization of winding insulation. For this reason, up to 20-30% of electric motors fail annually [1][2][3][4][5][6][7]. Our studies show that for air humidity of 100% and temperature of 35 °C, the insulation resistance R drops to a critical value of 0.5 MΩ within 9-10 days.…”
Section: Introductionmentioning
confidence: 94%
“…1 it may be concluded that TS, loaded by less than 30%, constitute approximately 80% of cases, among which 53% are loaded by less than 15%. Consequently, transformers operate with low efficiency [4,5] and high losses [14]. Fig.…”
Section: Regional Differencesmentioning
confidence: 99%
“…For entrepreneurs -reducing the cost of technological connectivity to electrical network. 4. For the population and businesses -the possibility of lowering or maintaining existing electricity prices, as well as reducing the cost of commercial and residential real estate by reducing the cost of construction of electricity networks.…”
Section: Regional Differencesmentioning
confidence: 99%
“…For example, the usual task of power supply systems with quiescent load is to reduce the short-circuit currents. This allows one to select the elements of the electrical network, designed for lower thermal and dynamic loads, to extend the service life of the switching protection equipment, to reduce capital investment and damage caused by an accident [6][7][8].…”
Section: Introductionmentioning
confidence: 99%